Kajian Literatur: Pengaruh Dukungan Emosional Keluarga terhadap Kesejahteraan Anak Usia Dini - Raisya Pasya Purwanto; Taopik Rahman; Risbon Sianturi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to analyze the influence of family emotional support on the well-being of early childhood. Early childood refrers to individuals agesd 0-8 years, known as the golden period of development, during which cognitive, social, adn emotional aspects grow rapidly. This research uses a literature review method by collecting and analyzing relevant scientific sources. The findings indicate that family emotional support, such as affection, attention, effective communication, adn positive parenting. Plays a significant role in enchacing childrens’s well-being. Children raised in supportive and harmonious family enviromrnts tend to have better emotional stability, higher emphaty, and well developed social skills. In contrast, a lack of emotional support may negatively affect chidren’s psyhocological development, leading to anxiety and difficulties in social interaction. Therefore, family emotional support is a crucial factor in shaping the overal well being of early childhood